Integrated Model of Character Education Development Based on Moral Integrative to Prevent Character Value Breaches - Rahmat Nur; Suardi .; Nursalam .; Hasnah Kanji (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to produce a model of strengthening character education in university. This study's substance problem is students' bad behavior, so it requires a more comprehensive model of supporting character education. The research used a mix-method. It is a combination of qualitative methods and quantitative methods. The qualitative research instrument uses the researcher himself as the main instrument, while the quantitative tool uses a validated questionnaire. Qualitative research uses purposive sampling and random sampling techniques for quantitative research data collection techniques using interviews, observation, questionnaires, and documentation. The qualitative data analysis stages were carried out by starting to reduce data, display data, and verify data. The research results on the integration model of character education development developed at the University of Muhammadiyah Makassar are integrated with moral integrations, namely knowing, feeling, sinverbal, action, habitus, and culture (KFSAHC) to prevent violations of character values.